Intoxicações exógenas por agrotóxicos : uma análise de registros ocorridos no Espírito Santo - Carvalho, Karla Patrício (2019)
The use of substances as pesticides occurs from the pre-industrial period. With the end of World War II and the emergence of mechanisms as chemical weapons, pesticides arose. With its use encouraged by the Green Revolution, the use of the products has become worldwide and especially in developing countries. Brazil is the world's largest consumer of pesticides and the highest number of cases of intoxication has been drawing attention to this problem. At present, the SINAN (National Aggravated Diseases Information System) receives the following information: exogenous by agrochemicals in a compulsory manner. Data from the Ministry of Health on the year 2007 and 2013. In this study, the confirmed cases of exogenous poisoning by pesticides in the State of Espirito Santo between 2007 and 2016. Descriptive analyzes of the socioeconomic and exposure-related parameters were done for the whole territory and for urban and rural areas. Linear and quadratic regression for analysis of temporal trend and communication of confirmed cases of decennial and quinquennial form. The criteria for participation in the analysis rate, the number of data, the confirmed and obvious cases of exogenous intoxication by pesticides in the state of Espírito Santo in the historical series. The study studied was predominantly male (n = 2457, 63.7%), in the age group 20-29 years (n = 936, 24.3%), and 30-39 years (n = 903; (N = 1166, 46.6%) and informal workers (n = 1166, 46.3%). The number of cases reported (n = 2457, 20.0%), confirmed cases (n = 1620, 65.9%), case fatality rate (n = 63, 0.9) and incidence rate Poisoning by agrochemicals is greater among men than among women. Intentional poisoning with suicidal motivation is greater in males. The chemical class of pesticides most involved in reported cases were insecticides, followed by acaricides and herbicides. The raticidal rates were 39% of the poisonings in the urban area and the pesticides of agricultural use by 85% in the rural area. Coropléticos maps were submitted to compulsory notification to approach the confirmed interviews to the cases that occurred. The study compared the profile of the population affected by the disease and the municipality is most affected by pesticide poisonings. An analysis of cases when linked to an urban or rural area with a proportion of urban and rural areas (51.8% and 48.2%), is, however, a rural area of 4.7 times larger than urban areas (200.9 and 43.1 per 100,000 ha respectively). The cases in urban session are in with the oldest years of study and in both sexes. In rural areas, low schooling is more frequent. The trend of increase in exogenous intoxications by pesticides in Espírito Santo, as the differences in socio-demographic characteristics and related to exposure and work in urban and rural areas show a seriousness of exogenous intoxications by pesticides in our state. This is it for personal activities for actions and actions that combat this aggravation.